2013
DOI: 10.1186/1742-2094-10-132
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin F2α FP receptor antagonist improves outcomes after experimental traumatic brain injury

Abstract: BackgroundInjuries to the brain promote upregulation of prostaglandins, notably the proinflammatory PGF2α, and overactivation of their cognate G-protein-coupled FP receptor, which could exacerbate neuronal damage. Our study is focused on investigation of the FP receptor as a target for novel neuroprotective drugs in a preclinical animal traumatic brain injury (TBI) model.MethodsAccordingly, the effects of acute intraperitoneal post-treatment with selective FP antagonist AL-8810 were studied in wildtype (WT) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 77 publications
(116 reference statements)
6
55
0
Order By: Relevance
“…Similarly, the underlying root cause of the impressive attenuation of the extent of post-injury glial activation observed in head-injured Cr2 -/- mice in this study (Figure  5) remains a topic of speculation. Recent studies have emphasized an important role for activated microglia and reactive astrocytosis in contributing to post-injury neuroinflammation and adverse outcomes [34-36]. A recently published experimental study using the controlled cortical impact (CCI) model in Wistar rats revealed that microglial activation after focal TBI peaked within the first three to seven days post injury which reflects a similar timeline of cellular activation observed in the present study [34].…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, the underlying root cause of the impressive attenuation of the extent of post-injury glial activation observed in head-injured Cr2 -/- mice in this study (Figure  5) remains a topic of speculation. Recent studies have emphasized an important role for activated microglia and reactive astrocytosis in contributing to post-injury neuroinflammation and adverse outcomes [34-36]. A recently published experimental study using the controlled cortical impact (CCI) model in Wistar rats revealed that microglial activation after focal TBI peaked within the first three to seven days post injury which reflects a similar timeline of cellular activation observed in the present study [34].…”
Section: Discussionsupporting
confidence: 82%
“…In addition, EP1 −/− mice have enhanced cerebral blood flow at reperfusion in a ischemic stroke model [34]. However, there are no significant morphological or anatomical differences in cerebrovascular vasculature between EP1 −/− and WT mice or between FP −/− and WT mice in our related studies [21], [34]. Vascular damage plays an important role in TBI and is a primary cause of ICH, which correlates with TBI severity [61] and triggers secondary biochemical cascades, exacerbating primary injury involving several events associated with disrupted Ca 2+ signaling such as extensive glutamate release and calpain-dependent cortical necrosis [61]–[64].…”
Section: Discussionmentioning
confidence: 59%
“…However, our most recent data documented that systemic administration of a selective FP receptor antagonist significantly improved anatomical and functional outcomes in various brain injury models, both in vivo and in vitro, including ischemic stroke, excitotoxicity, and TBI, and the selectivity of an FP antagonist was confirmed in genetic knockout mice lacking the FP receptor (FP −/− ) [17], [19][21], [23]. Based on the data from our group and others, the roles of prostaglandin receptors are complex and the outcomes of inhibition or genetic deletion of some of these receptors, such as EP1, may have the opposite effects in different neurological conditions such as ischemic and hemorrhagic strokes [19], [22][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This task was designed to assess neuromuscular function and muscular strength by sensing the maximal peak force of the mouse forelimb [3234]. Muscle strength was measured using a Grip Strength Meter (San Diego instruments Inc., San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%